2012
DOI: 10.1155/2012/154743
|View full text |Cite
|
Sign up to set email alerts
|

Human Schistosome Infection and Allergic Sensitisation

Abstract: Several field studies have reported an inverse relationship between the prevalence of helminth infections and that of allergic sensitisation/atopy. Recent studies show that immune responses induced by helminth parasites are, to an extent, comparable to allergic sensitisation. However, helminth products induce regulatory responses capable of inhibiting not only antiparasite immune responses, but also allergic sensitisation. The relative effects of this immunomodulation on the development of protective schistoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 241 publications
(268 reference statements)
1
9
0
Order By: Relevance
“…Further follow-up with an ultrasound scan would be beneficial and further bio-chemical evaluation of the ascitic fluid would be very valuable [42]. Contrary to previous reports of an inverse relationship between schistosomiasis and atopy, infected children had a 6-fold higher odds of presenting with atopy [6,43,44]. It has been reported that schistosomiasis in PSAC is usually at low intensities and this might explain why we had a positive relation [5].…”
Section: Discussionmentioning
confidence: 74%
“…Further follow-up with an ultrasound scan would be beneficial and further bio-chemical evaluation of the ascitic fluid would be very valuable [42]. Contrary to previous reports of an inverse relationship between schistosomiasis and atopy, infected children had a 6-fold higher odds of presenting with atopy [6,43,44]. It has been reported that schistosomiasis in PSAC is usually at low intensities and this might explain why we had a positive relation [5].…”
Section: Discussionmentioning
confidence: 74%
“…Early schistosome infections, before patency, induce host immunity of the T helper type 1 (Th1) type involving interferon‐ γ and tumour necrosis factor‐ α . However, both acute S. mansoni infection and sensitization by allergens evoke similar immune responses that are Th2‐biased and characterized by the release of cytokines such as interleukin‐4 (IL‐4), IL‐5 and IL‐13, eosinophilia, and production of IgE antibodies . Chronic and advanced stages of infection are characterized also by Th2 immunity, but in a form that is ‘modified or ‘modulated’ and that evokes regulatory T‐cell activity and production of cytokines such as IL‐10 and transforming growth factor‐ β , which curb excessive inflammatory responses and so enhance survival of the parasite and perhaps that of the host also .…”
Section: Introductionmentioning
confidence: 99%
“…4 However, both acute S. mansoni infection and sensitization by allergens evoke similar immune responses that are Th2-biased and characterized by the release of cytokines such as interleukin-4 (IL-4), IL-5 and IL-13, eosinophilia, and production of IgE antibodies. 5,6 Chronic and advanced stages of infection are characterized also by Th2 immunity, but in a form that is 'modified or 'modulated' and that evokes regulatory T-cell activity and production of cytokines such as IL-10 and transforming growth factorb, which curb excessive inflammatory responses and so enhance survival of the parasite and perhaps that of the host also. 4,7,8 Incidentally, the characteristics of immunomodulated anti-parasite Th2 immunity are to some extent similar to those that pertain after successful immunotherapy of allergic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The average intensity of infection of Ascaris lumbricoides and Trichuris trichiura rises in children aged 5-15 years and declines in intensity and frequency in adulthood [16] while hookworm often displays a firm rise in the intensity of infection with age which peaks up in adulthood [17].…”
Section: Introductionmentioning
confidence: 99%